Meningen der gik tabt - Nielsen Hansen, Robert Bonde (Dansk Teologisk Tidsskrift, 2010)
Until a couple of decades ago, few scholars of the liturgy of the early church doubted that the Eucharistic and Baptismal rites of the early church could be traced back to the institution of these rites by Jesus Christ, or the Apostles in Jerusalem around the year 30. This view has in later years been challenged, and it is today commonly held that we are unable to reconstruct a primordial rite dating back to Jesus or the Apostles. Supposedly, we are also unable to find common elements in the earliest Christian rites, which appear to be solely regional phenomena. Even though this latter view may to a large extent be true, this article argues that the semantics of minimalism used to describe the liturgy should be supplemented with an acknowledgement of commonly shared themes in the material. Following this line of inquiry, I suggest that whereas one cannot trace the Eucharistic and Baptismal rites of the 2nd century back to Jesus, they nonetheless have a number of elements in common, namely eschatological and sacrificial themes.